PENGGUNAAN MEDIA GAMBAR BERSERI UNTUK MENINGKATKAN KEMAMPUAN MENULIS NARASI SISWA KELAS IV SEKOLAH DASAR - Kurniati, Agusta; Warkintin, Warkintin; Oktaviani, Ursula Dwi; Nurahim, Nurahim (STKIP Persada Khatulistiwa Sintang, 2025)
This Classroom Action Research aims to improve narrative writing skills using a series of pictures as media among fourth-grade students in the Indonesian language subject at the elementary school level. The research employed a qualitative descriptive method, involving 11 fourth-grade students of SD Negeri 02 Nobal in the 2023/2024 academic year as research subjects. Data collection techniques included teacher and student observation, tests, and interviews. Data analysis was conducted using the Miles and Huberman model. The results of the study are as follows: (a) The use of picture series media in the learning process was effective, as evidenced by student learning activities in Cycle I with an average of 55.76% (categorized as fair). In Cycle II, the average student activity increased to 84.54% (categorized as good), indicating an improvement of 28.78%. (b) Students’ learning outcomes from the narrative writing test in Cycle I showed an average score of 61.82 with a classical completeness of 63.63% (fair category), while in Cycle II, the average score rose to 83.62 with a classical completeness of 90.9% (very good category). (c) Students responded very positively to the use of picture series media, as evidenced by their enjoyment of learning Indonesian using this medium.